OCCUPATIONAL HEALTH AND SAFETY PRACTICE AND EMPLOYEES’ JOB COMMITMENT IN DUFIL NIGERIA LIMITED, OTA,OGUN STATE, NIGERIA - Adekoya, Emmanuel Olawale; Jayeoba, Foluso Ilesanmi; Fapohunda, Tinuke Moradeke (Journals Park Publishing, 2022)
This study investigated the relationship between occupational health and safety practice and employees’ job commitment in Dufil Nigeria Limited, Ota, Ogun State. The study adopted descriptive survey research design and selected 168 respondents from the population of four hundred and eighty six (486) using purposive sampling method. Three hypotheses were tested using Pearson Product Moment Correlation Coefficient with the aid of SPSS version 20. The first hypothesis indicated a strong and positive statistically significant relationship between organisational environment and affective commitment, also, the second hypothesis revealed a positive and statistically significant relationship between employees’ safety communication and continuance commitment, while, the third hypothesis established moderate and significant relationship between safety practice and normative commitment. Arising from the findings, it was recommended, among other things, that there is need for Dufil Nigeria Limited management and other employers of labour to create more awareness through safety education and encourage the execution of occupational health and safety policies and practices amongst its workers so as to enhance their loyalty and commitment. Organisations are to make sure that safety managers and other top management staff, as well as employees, are held accountable for safety breaches and appropriate disciplinary measures taken to guide against future occurrences of any action that can be hazardous to the health and safety of employees’ in the course of their duties in the organisation.
Keywords: Affective Commitment, Continuance Commitment, Normative Commitment, Occupational Health and Safety Practice.